Knowledge, Attitude, and Performance of Nurses\' Crisis Management in Natural Disasters in Yazd City - Tahere Soltani; Mohammad Hossein Baghianimoghadam; Mohammad Hassan Ehrampoush; Najmeh Baghian; Abdolkhalegh Jafari (Shahid Sadoughi University of Medical Sciences, 2016)
Abstract: Introduction: Natural disasters are considered as events that are beyond human control and usually result in death and different injuries; they also significantly affect public health. The lack of proper sanitation and communal life creates numerous problems. The aim of this study was to determine the knowledge, attitudes, and performance of nurses (since nurses work more than others in disasters) in disaster management. Materials & Methods: This was a cross–sectional and descriptive study. The 220 participants of this study were selected by stratified random sampling method. Data was collected by questionnaire taken from similar studies in the field of nursing whose reliability was confirmed by the relevant specialists and its validity was confirmed by Cronbach's alpha (0.83). Data analyses included Spearman test, analysis of different levels of the independent variables (Mann-Whitney, Kruskal-Wallis test) or t- test, and comparing means as well as the related data (non-parametric). Results: In this study, the average age of staff was 33.94±6.4 and years of their work experience was 10.5 ±7.14. The nurses' average level of knowledge about crisis management was 13.05±5.24 out of 22.  The mean grade scores of attitude to crisis management was 28.94±3.39 out of 33, further, their function in crisis management was 45.88±6.5 out of 57. Discussion: Due to the increased frequency of occurrence and consequences of the disaster and the special role of health care services before, during, and after the occurrence of such incidents, the results were not suitable. Then, it was concluded that proper preparation is essential for nurses as the largest providers of information and health services to people, so their performance must be measured which is the objective of this study.